TRIGONOMETRIC APPROACH TO CURVED PSEUDO ELASTIC IMPEDANCE (CPEI) AND PSEUDO ELASTIC IMPEDANCE â LITHOLOGY (PEI-L) ATTRIBUTES FOR RESERVOIR CHARACTERIZATION IN THE âCLâ FIELD, EAST NATUNA BASIN - La Tansa Millata Hanifah, Cut
One of the basins that needs to be explored and optimized with considerable hydrocarbon potential is the East Natuna Basin. This research focuses on the “CL” field in the Lower Terumbu and Gabus formations at depths of 8617.52-8735.06 ft and 9239.89 - 9360.18 ft, respectively. The purpose of this study is to characterize hydrocarbon reservoirs using the Curved Pseudo Elastic Impedance (CPEI) and Pseudo Elastic Impedance-Lithology (PEI-L) trigonometric approaches. The data available in this study are well data (CLT-1 and CLT-2), partial stack seismic data, and horizon data. The seismic data generated P and S reflectivity volumes through the Amplitude Versus Offset (AVO) equation by Ursenbach-Stewart. Analysis of the well logs showed sensitive elastic parameters are Acoustic Impedance (AI) and Vp/Vs ratio to separate lithology and fluid. The inversion seismic method uses Linear Programming Sparse Spike (LPSS) for AI inversion analysis, and Vp/Vs ratio through AI/SI and Extended Elastic Impedance (EEI). The volume Vp/Vs ratio has better results using EEI inversion. However, the inversion results of elastic parameters generally show a linear trend. Meanwhile, petrophysical parameters such as porosity and water saturation have non-linear trends in Rock Physics Template (RPTs). Therefore, the seismic inversion results have not depicted the distribution of hydrocarbons. This results in the need for a trigonometric approach using the CPEI and PEI-L attributes to be able to characterize the reservoir. The CPEI attribute is used to project water saturation, and the PEI-L attribute is used to project porosity. The results show that low AI, Vp/Vs ratio, CPEI, and PEIL, and high porosity indicate a target zone containing hydrocarbons.